PENGARUH PEMBERIAN UPAH DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT DARIA DHARMA PRATAMA IPUH - Erwin Erwin; Khairul Bahrun (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aimed to determine the effect of wages and incentives toward employees’ productivity of PT Daria Dharma Pratama Ipuh, Muko Muko Regency. The object of this study was the 65 employees of PT Daria Dharma Pratama Ipuh, Mukomuko Regency. This study used observation and questionnaire as techniques of collecting data. There are several data analysis techniques used in this research, including using instrument test, classical assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. The results of the tests that have been carried out, it can be concluded that the variables of Wages (X1) and Incentives (X2) have partial or simultaneous effect toward employees’ productivity at PT Daria Dharma Pratama Ipuh Mukomuko regency. From the results of the multiple linear regression test, the regression equation is obtained Y = 1.275 + 0.693 (X1) + 0.528 (X2).